Scientific production and collaborative networks in Peruvian Social Security (EsSalud): Bibliometric analysis 2008-2020 - Alarcón-Ruiz, Christoper A: (2021)
Background: Scientific production of Social Security in Perú (EsSalud) has progressively increased. However, there is no description of its scientific production and collaboration networks in relevant international databases. Objectives: Describe the scientific production of EsSalud in indexed journals during the 2008-2020 period. Material and Methods: Bibliometric study that evaluated scientific articles and meeting abstracts, with at least one institutional affiliation related to EsSalud among its authors, indexed in the Scopus, Web of Science, Ovid-Medline, or Scielo Citation Index databases published during the period 2008-2020. The total annual scientific production is reported and separately according to base. Intra and extra-institutional collaboration networks were evaluated. Results: 4159 records were obtained and, after applying the selection criteria, 2333 articles remained. Scientific production from all databases, except for the Scielo Citation Index, had a progressive increase. Most of articles were original, observational, and self-funded. Two national hospitals from EsSalud accounted for almost two-thirds of all analyzed scientific production. Institutions from Lima had little collaboration with other institutions from other regions, leading to little interregional collaboration. On the other side, there was a noticeable collaboration with local universities. The medical area that was most addressed by scientific publications was that related to clinical medicine specialties. Conclusions: EsSalud's scientific production number and quality had increased during last years in collaboration with local universities. It is important to promote initiatives thar boost the research and collaboration within EsSalud's institutions, emphasizing research priorities and the leading causes of national morbidity and mortality.